Thermo-mechanical XFEM-type modeling of laminated structure with thin inner layer. (1st October 2015) - Jaśkowiec, J.; Pluciński, P.; Pamin, J.
Highlights: Computational 3D thermo-mechanical modeling of laminated composites is proposed. Coupled FE formulation is derived for a laminate with thin inner layer. XFEM is used to represent integrals over the thin inner layer. Space discretization of thin layer is avoided, coarse mesh provides good accuracy. Approach is robust in non-stationary thermo-mechanical analysis of laminated glass. Abstract: The paper deals with three-dimensional numerical thermo-mechanical modeling of a laminated structure with very thin inner layer. A typical example of such a structure is two-ply laminated glass where a polyvinyl butyral thin layer is between the glass plies. The numerical model of such a structure is based here on the extended finite element method (XFEM) that is applied for both the mechanical and thermal parts of the model. In the approach the glass volume is spatially discretized using XFEM with discontinuity across the inner layer. The thin inner layer is modeled only by an integral over its volume, that is why the approach is called Inner Integral FEM. Owing to the approach the laminated structure can be meshed not regarding the thin inner layer. The correct results are obtained even for coarse discretization. The approach is illustrated with a couple of examples where the mechanical, thermal and non-stationary coupled thermo-mechanical problems for two-ply laminated glass are considered.